KEBIJAKAN PEMERINTAH DAERAH DALAM MENINGKATKAN SISTEM RUJUKAN KESEHATAN DAERAH KEPULAUAN DI KABUPATEN LINGGA PROVINSI KEPULAUAN RIAU - Ignasius Luti; Mubasysyir Hasanbasri; Lutfan Lazuardi (Center for Health Policy and Management, 2012)
Ignasius Luti1, Mubasysyir Hasanbasri2, Lutfan Lazuardi21 Dinas Kesehatan Kabupaten Lingga, Kepulauan Riau2 Program Studi Ilmu Kesehatan Masyarakat, Fakultas Kedokteran,Universitas Gadjah Mada, YogyakartaABSRACTBackground: One of the critical issues in the development ofnational health care is the limited accessibility to health services.Such problems also occur in Linga District of KepulauanRiau Province. It is caused by many factors, such as geographicallocation, cost, number of health personnel and conditionof health care facilities, such as health centers and theirnetworks which are not accessible to the public. Several attemptshave been made, for example, by improving the statusof sub-health centers to be health centers, health centers tobe treatment centers, assinging health workers both medicaland paramedical, improving health financing and making budgetpolicies. However, its implementation has not been maximal.In accordance with the above background, it would requirea study on the role of local government policy in improvingthe referral system which is useful to know the problemsin the field, so that in the future a variety of improvement canbe done.Objective: To determine the referral system in the islandsarea of Linga District.Methods: This was a case-study research. The researchsubjects were head of health centers / health center doctors,nurses/midwife assistants, ambulance drivers/sea ambulancedrivers, patient families, community figures, jamkesmas/Jamkesda managers, head of health care section/head ofhealth office, director of local hospital/mobile hospital and emergencyroom nurses. The variables in this study were independentvariable (referral system) and dependent variable (ambulanceservice). The research location was in Linga Districtof Kepualauan Riau Province.Results: The results showed that policy efforts of the LingaGovernment District in improving the referral system had existed.The existing financing policy had encompassed twoaspects both from the demand side (medical expenses) andfrom the supply side (a system that supported health care).The process of referral from primary care to advanced serviceshad been going well although there was still lack as theunavailability and completeness of services. Most of the healthworkers had received training; there were also specialist doctors(in collaboration with the faculty of medicine), but networkingin the referral process was done partially and notintegrated.Conclusion: The health referral system in Linga District hadrun pretty well, but did not fully involve community participationin an integrated service system. The local government in thiscase Linga District Health Office needs to revitalize as well asaccelerate the development of Desa Siaga (alert villages) readinessto increase community participation in the developmentof a referral system.Keywords: policy, referral systems, islands, ambulance service